Monoclinic honeycomb-layered compound Li3Ni2SbO6: preparation, crystal structure and magnetic properties - Zvereva, Elena A.; Klingeler, Rüdiger (Dalton transactions, 2012)
Two synthetic routes—ion-exchange preparation from layered Na3Ni2SbO6 at 300 °C and direct solid-state synthesis at 1150 °C resulted in layered Li3Ni2SbO6, a cation-ordered derivative from the rocksalt type. The Fddd form reported earlier could not be reproduced. According to the XRD Rietveld analysis, Li3Ni2SbO6 is a pseudohexagonal monoclinic structure, C2/m, with a = 5.1828(2) Å, b = 8.9677(3) Å, c = 5.1577(2) Å, β = 109.696(2)°. No Li/Ni mixed occupancy was detected. At high temperatures, the magnetic susceptibility follows the Curie-Weiss law with a positive value of Weiss temperature, ∼8 K, indicating a predominance of ferromagnetic interactions. However, Li3Ni2SbO6 orders antiferromagnetically at TN ∼ 15 K. The effective magnetic moment is 4.3 μB/f.u. which satisfactorily agrees with theoretical estimations assuming high-spin configuration of Ni2+ (S = 1). Electron spin resonance (ESR) spectra show single Lorentzian shape line attributed to Ni2+ion in octahedral coordination. The absorption is characterized by isotropic temperature independent effective g-factor g = 2.150 ± 0.005. In accordance with the layered honeycomb crystal structure determined for Li3Ni2SbO6, the superexchange interaction between Ni2+ ions through Ni-O-Ni pathways within Ni2SbO6 layers are assumed to be ferromagnetic, while the dominant interaction between layers is antiferromagnetic.